The Role of Albumin and Hemoglobin as Predictors of 28-day Mortality in Elderly Sepsis Patients in Mohammad Hoesin Hospital Palembang - Gultom, Widya Mandala Sari; Riviati, Nur; Perdana, Rizky; Husin, Syarif (UI Scholars Hub, 2021)
Introduction. Sepsis is defined as organ dysfunction caused by dysregulation of the host’s response to infection. The majority of sepsis are experienced by elderly patients with high mortality rates. In the condition of sepsis, there are various body mechanisms that cause a decrease in albumin and hemoglobin. This study is to determine the predictive value of albumin and hemoglobin levels on 28-day mortality of elderly sepsis patients.